2010
DOI: 10.1177/0886260510388284
|View full text |Cite
|
Sign up to set email alerts
|

PTSD Symptoms and Sexual Harassment: The Role of Attributions and Perceived Control

Abstract: Researchers have compiled significant evidence demonstrating that sexual harassment leads to psychological harm, including the full symptom picture of PTSD, but few have examined the psychological processes involved. Research on attributions among trauma victims would suggest that causal attributions and perceptions of control may be important predictors of outcomes. The authors discuss a study involving a path model that used data from 189 women involved in sexual harassment litigation. Results indicate that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 26 publications
1
42
0
1
Order By: Relevance
“…A nationally representative study of women in the U.S. found that one in fi ve self-identifi ed sexual harassment victims met criteria for a DSM-IV diagnosis of Major Depressive Disorder, and one in ten reported symptoms of Posttraumatic Stress Disorder (PTSD; Dansky and Kilpatrick 1997 ). Recent research also fi nds that women who experience sexual harassment (self-identifi ed or not) report PTSD symptoms (Larsen and Fitzgerald 2011 ). Sexual harassment has also been connected to the use and abuse of alcohol and other drugs (Richman et al 2002 ;Rospenda et al 2009 ).…”
Section: Implications For Working Women's Wellbeingmentioning
confidence: 99%
“…A nationally representative study of women in the U.S. found that one in fi ve self-identifi ed sexual harassment victims met criteria for a DSM-IV diagnosis of Major Depressive Disorder, and one in ten reported symptoms of Posttraumatic Stress Disorder (PTSD; Dansky and Kilpatrick 1997 ). Recent research also fi nds that women who experience sexual harassment (self-identifi ed or not) report PTSD symptoms (Larsen and Fitzgerald 2011 ). Sexual harassment has also been connected to the use and abuse of alcohol and other drugs (Richman et al 2002 ;Rospenda et al 2009 ).…”
Section: Implications For Working Women's Wellbeingmentioning
confidence: 99%
“…Three older studies of post-settlement outcomes for grievants compared to non-grievants (in a range of workplace complaints), demonstrated that those who had made a complaint had lower performance ratings, promotion rates and attendance rates, and higher quit rates in the year following the grievance (Klaas and DeNisi 1989;Lewin and Peterson 1988). Another exception stems from Larsen and Fitzgerald's (2011) argument that in assisting complainants to recover, it is important to minimize the focus on blaming the harasser, which decreases a sense of control over the present, and diverts attention to controllable aspects of recovery. One exception is Oppenheimer's (2004) recommendation of proactive and longer-term follow-up with both the complainant and the respondent to ensure that retaliation had not occurred.…”
Section: Tertiary Interventionmentioning
confidence: 99%
“…Several cross-sectional studies have found evidence of symptoms and diagnosis of PTSD among workers exposed to workplace bullying and sexual harassment [Leymann and Gustafsson 1996, Schneider, et al 1997, Mikkelsen and Einarsen 2002, Matthiesen and Einarsen 2004, Tehrani 2004, Willness, et al 2007, Buchanan and Fitzgerald 2008, Larsen and Fitzgerald 2010, Rodríguez-Muñoz, et al 2010]. In explaining how bullying may lead to PTSD, Einarsen and colleague (2003) posit that although the experience of workplace injustice is often not life-threatening, the experience threatens the inner world of the target by shattering basic cognitive schema about fairness and justice and negatively influences one's social and personal identity leading to PTSD.…”
Section: Outcomes: Contributions Of Injustice To Health Disparitesmentioning
confidence: 99%